2004
DOI: 10.1111/j.1475-6773.2004.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Medicare Payment Changes on Nursing Home Staffing and Deficiencies

Abstract: Medicare's PPS system and associated rate cuts for SNFs have had a negative effect on staffing and regulatory compliance. Further research is necessary to determine whether these changes are associated with worse outcomes. Findings from this investigation could help guide policy modifications that support the provision of quality nursing home care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(133 citation statements)
references
References 19 publications
4
129
0
Order By: Relevance
“…No major Medicare payment policy changes occurred during the study period, which have been found to influence quality of care in the nursing home [95][96]. In addition, to my knowledge, there were no changes in nursing home regulations during this time period.…”
Section: Limitationsmentioning
confidence: 96%
See 2 more Smart Citations
“…No major Medicare payment policy changes occurred during the study period, which have been found to influence quality of care in the nursing home [95][96]. In addition, to my knowledge, there were no changes in nursing home regulations during this time period.…”
Section: Limitationsmentioning
confidence: 96%
“…Among for-profit nursing homes, the elimination of cost reimbursement was associated with a larger drop in nurse staffing [95]. Konetzka et al found that professional staffing decreased and regulatory deficiencies increased with PPS, and the effects increased with the percent of Medicare residents in the facility, except in facilities with the highest proportions of Medicare residents [96]. In addition, after the implementation of Medicare PPS, compared with non-profit SNFs, for-profit SNFs dramatically altered the services they provided in response to new financial incentives by decreasing the percentage of residents receiving extremely high levels of rehabilitation therapy [97].…”
Section: Differences Of Nursing Home Behavior In Response To Changes mentioning
confidence: 99%
See 1 more Smart Citation
“…Improved methods to control for changes in quality and to cope with the potential endogeneity of output and/or quality in cost functions have been proposed (Gertler and Waldman, 1992;Chen and Shea, 2002). Also, direct assessment of the impact of PPS on quality (Konetzka et al, 2004;Konetzka et al, 2006) and access to nursing care (Coburn et al, 1993) have been carried out.…”
Section: Previous Research On the Impact Of Pps In Nursing Home Carementioning
confidence: 99%
“…Using data on U.S. NHs over the period 1996-2000, Konetzka et al (2004) study the impact of PPS on quality by applying a di¤erence-in-di¤erence approach and a negative binomial model. The authors use changes in the professional sta¢ ng and the number of regulatory de…ciencies as proxies for quality.…”
Section: Previous Research On the Impact Of Pps In Nursing Home Carementioning
confidence: 99%